Significant oil palm diseases impeding global industry : a review - Mohd Amar Shafiq Saipol Anuar; Nusaibah Syd Ali (Penerbit Universiti Kebangsaan Malaysia, 2022)
Oil palm is the most well-known high yielding and versatile oil crop grown. In 2019, Malaysia ranked as the world’s second largest producer of palm oil products (28%) after Indonesia (57%), contributing around USD 9.07 billion to the country’s Gross Domestic Product (GDP) and has been the main economic contributor in the agriculture sector. In recent years, increase in demand has paralleled production. However, pests and diseases have been the major constraints in production causing reduction in palm oil quality and yield. This paper reviews a current status of oil palm diseases of significant economic importance affecting the global oil palm industry. Plant diseases such as basal stem rot (BSR), Fusarium wilt, Phytophthora bud rot, Pestalotiopsis leaf spot, common spear rot, orange spotting and upper stem rot (USR) have been classified as the major diseases of oil palm in terms of economic importance. This paper discusses on the damages caused by the diseases, the causal pathogens and pathogenicity, symptoms as well as treatments or control in the view of developing measures to manage occurrences.